PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT NASMOCO MAJAPAHIT SEMARANG - Eva Aniniawati, 15.05.51.0281; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of the Work Environment and Compensation on Employee Performance at PT. Naroco Majapahit Semarang. The research location at PT. Naroco Majapahit Semarang, with a sample size of 90 respondents. The sampling method used is the census method. The analysis tool used is multiple regression, as for testing the hypothesis using the level of sig <0.05. Data collection by measurement using a Likert scale 5 (five) alternative answers. The results showed that the work environment has a positive and significant effect on employee performance, Compensation has a positive and significant effect on employee performance.